Mobilization Of Resources For Development (American Journal of Islam and Society, 1989)
IntroductionThe employment of resources is important for any aspect of the spectrumof overall development, be it economic or non-economic, spiritual or material.Although spiritual matters seem to be noneconomic in nature, their inculcationand development involve the use of resources. Hence, Allah (SWT) instructsmankind to invest in the development of spiritual values. The spread andestablishment of Islam require travelling, dissemination of knowledge,education, publication of literatw~u, se of media, protecton of Islamic societiesfrom non-Islamic forces (i.e. internal and external defense), administrationof institutions intended for the implementation of Islamic obligations andnorms, and the like. Each of these functions requires tremendous amountsof material and human resources.Economic development comprises two essential components: economicgrowth and equity in the distribution of income and wealth. Economic growthrequires investable resources for producing capital goods, hiring workers andmanagers, acquiring raw materials, improving technology, and organizingthe production process. In particular, capital formation and technologicalchange have been considered as key factors in economic development; theavailability of adequate investable resources is a prerequisite for the smoothsupply and use of these factors.The Islamic code of life provides enormous incentives for mobilizingresources, both material and human, and an institutional framework conduciveto efficient use of resources for development. This paper, which concentrateson mobilizing resources for development, discusses natural, human andfinancial resources, as well as the role of government and internal and externalinstitutions in the development process ...